Some Indications Of Large Abdominal Fluid In Aseptic Pododematitis In Cows - X.H.Eshkuvatov; H.B.Niyozov (Genius Publishing Group, 2023)
This article presents an examination of large abdominal fluid pH disorder and large abdominal movement changes in aseptic pododermatitis in cattle hooves of the breed.
Keywords: Pododermatitis; abdominal fluids; pH; rumination